Analisis Dampak Wisata Peridon terhadap Perekonomian Masyarakat di Desa Aek Nabirong Kecamatan Koto Balingka Kabupaten Pasaman Barat - Ahsana Nadya; Andriyaldi Andriyaldi (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study is influenced by the importance of the tourism sector as one of the main drivers of regional economic growth, particularly in rural areas. There is considerable tourism potential in Pasaman Barat Regency, Koto Balingka District, specifically in Aek Nabirong Village. This destination not only offers natural beauty that attracts visitors but also creates economic opportunities for the surrounding community. The purpose of this research is to analyze the impact of Peridon Tourism on the overall economic condition of Aek Nabirong Village and to identify both direct and indirect effects of tourism on local income. The research method employed is a qualitative approach, with data obtained through observation, interviews, and documentation involving local communities, business actors, and tourism stakeholders. The findings indicate that Peridon Tourism contributes to increasing community income through culinary businesses, rental of tourism facilities, and employment opportunities in the tourism area. In addition, the presence of this destination opens up new business opportunities for local residents. However, several challenges remain in its development, including unstable visitor numbers each year, limited supporting facilities, and difficult road access.